Peran inspektorat dalam mewujudkan pengelolaan dana desa yang akuntabel di Kabupaten Kepulauan Talaud - Manumbalang, Ireynda; Tinangon, Jantje J.; Kalalo, Meily Y. B. (Riset Akuntansi dan Portofolio Investasi, 2025)
This study aims to determine the role of the Inspectorate in realizing accountable village fund management in the Talaud Islands Regency. The type of research used is qualitative with a descriptive approach. The results of research on the role of the Inspectorate in realizing accountable village fund management are (1) Inspection, carried out according to the provisions. (2) Review, review of planning documents and their implementation by examining the SPJ. (3) Monitoring, checking planning documents, monitoring implementation and final monitoring (4) Evaluation, ensuring transparency by making information boards, billboards related to the realization of the activity budget and the completeness of the accountability report (5) Guidance, carried out by training technical guidance, and consultation regarding the management of village funds, has been in accordance with applicable laws and regulations.